Prop tricks - Turnbull, Stephanie (Mankato, Minn. : Smart Apple Media, 2012)
"Teaches how to perform magic tricks with the use of props such as silks, balloons, ropes, and hoops. Includes step-by-step instructions, picture diagrams, and performance tips"--Provided by publisher.
Teaches how to perform magic tricks with the use of such props as silks, balloons, ropes, and hoops.
Includes index.
Keywords: Magic tricks -- Juvenile literature; Stage props -- Juvenile literature; Magic tricks; Stage props; Magic tricks